Identifikasi dan prevalensi ektoparasit pada ikan Nila (Oreochromis niloticus) di kolam budidaya Kampung Hiung, Kecamatan Manganitu, Kabupaten Kepulauan Sangihe - Manurung, Usy N; Gaghenggang, Fatmawati (Universitas Sam Ratulangi, 2016)
A research had been conducted to identify and analyze the prevalence of ectoparasites on Nile tilapia (Oreochromis niloticus) cultured in Kampung Hiung, Manganitu District of Sangihe Island Regency during May 2016. Identification was conducted at The Laboratory of Fisheries and Maritime, Polytechnic of Negeri Nusa Utara.Â The research found five parasite species infecting nile tilapia including Dactylogyrus sp, Oodinum sp, Lerneae sp, Gyrodactylus sp and Trichodina sp. The highest prevalence value was Dactylogyrus sp (86.67%), followed by Oodinium sp (33,33 %), Lerneae sp (13,33%), Gyrodactylus sp (6.67%) and Trichodina sp (6.67%) Keywords:Â parasite, identification, prevalence, Oreochromis niloticus